TRAINING OF INTERIOR COMPANY TO STUDENTS OF SMSR PADANG (SMK N 4 PADANG) - Malik, Kendall (Batoboh, 2019)
Opening the design department at SMKN 4 / SMSR Padang is a good and progressive step for this school. Many people have understood about designs such as: kitchen set design, living room, family room and others. It is a good opportunity for students of  SMKN 4 / SMSR Padang.  The student will be able to open their own job by the presence of applications for interior design. Responding to the important role of design schools in Padang is an effort in solving design problems in our community environment, especially in Padang. It has become awareness for all of us both from the school and stakeholders, that design graduates are the heart of a company. By providing counseling about these design principles, teachers and students can understand the importance of environmental design around us and should be applied in a tangible (three-dimensional) form.